Identification and Incidence of Spina Bifida during Gestation and its Pregnancy Outcomes - Kailash Kumar Daseja, Kaneez Fatima, Akhtar Hussain Phul, Naimatullah Bozdar, Jia Dodani, Shahzeb (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To identify the incidence of spina bifida during gestation and its pregnancy outcomes. Study design: Cohort study Place and duration of study: Department of Radiology, Chandka Medical College Hospital, Larkana from 1st October 2020 to 30th September 2022 Methodology: One thousand pregnant women who were screened for the identification of spina bifida. Doppler based ultrasonography was performed in each patient. The fetus body was examined during sonography Doppler between 18-24 weeks. The body of the fetus was focused and visualized longitudinally in midsagittal section. Spinal cord was traced from neck to sacral, cervical vertebra and thorax. A tram track appearance was observed. Spinal nerve positioning was also observed. In spina bifida nerve tethering was seen. The primary outcomes in reference to baby weight and maturity were recorded while secondary outcomes of the fetuses in terms of any disability were followed up to 12 months of age. Results: The mean age of the women was 25.6±5.6 years. The incidence of spina bifida was 1.1%. Within the primary outcomes observed birth weight ranged within 3.1-3.5kg. Around 81.81% cases were born full term while 18.18 were premature. On 06 months’ follow-up of the spina bifida cases it was observed that 45.45% of new born suffered from skin problems as sores, calluses or and blisters while 36.36% had hydrocephalus with excessive CSF which needed monitoring. Mobility issue and disability was observed in 27.27% cases. Conclusion: Spina bifida cases are identified successfully within gestational period. Prematurity can be significantly noticed in spina bifida cases. The lumbosacral and lumbar lesions are most common as well as skin conditions and hydrocephalus. Key words: Incidence, Spina bifida, Gestation, Outcome